Synthesis of iron oxide catalysts using various methods for the spin conversion of hydrogen - Das, Taraknath; Nah, In Wook; Choi, Jeong-Gil; Oh, In-Hwan (SPRINGER, 2016)
A series of alpha-Fe2O3 catalysts were synthesized using various methods such as incipient wetness impregnation, soft templating, hard templating, precipitation and citrate sol-gel. The surface morphology and crystallite sizes were characterized by SEM, XRD and Raman spectroscopy. The spin conversion of ortho hydrogen to para hydrogen was studied using in situ FTIR spectroscopy at cryogenic temperature (17 K). The spin conversion was very slow and time dependent. The spin conversion was also strongly dependent on the crystallite size of alpha-Fe2O3 and the methods of synthesis. The catalyst synthesized by precipitation method possessed the highest spin conversion similar to 99.9 % after 45 min of interaction. The catalyst synthesized by templating methods showed average activity. The catalyst synthesized by the citrate sol-gel method showed very poor activity due to formation of larger crystallite sizes.
Keywords: PASADENA HYPERPOLARIZATION; HYDROTHERMAL SYNTHESIS; MESOPOROUS MATERIALS; ALPHA-FE2O3; NANOPARTICLES; FE2O3; PERFORMANCE; CONVERTER; NANOSTRUCTURES; SPECTROSCOPY